Diagnosis of virus Zika infection - Cabezas, César (2017)
Zika virus is an RNA virus whose infection can have as complications congenital syndrome and Guillain Barré syndrome. As there are other arboviruses that present with fever and rash it is important to have a syndromic approach for testing and laboratory diagnosis. Currently real time RT-PCR and virus isolation are available as standards for confirmatory diagnosis in the early days of infection. The serological tests (ELISA, NP) to determine IgM antibodies have the disadvantage of cross-reactions with other flaviviruses, though they may be used in certain circumstances where it is not possible to have RT-PCR and a proper interpretation.